Phytochemical screening of leaf extracts of arka kiran var. of guava - Gurusamy, K (Bangladesh Journal of Botany, 2023)
In the present study the presence of phytochemicals, and in vitro antioxidant activities of ethanolic leaves extract of Psidium guajava Linn variety namely Arka kiran was investigated.The ethanolic leaf extract of Arka kiran was found to processes secondary metabolites of alkaloids, flavonoids, saponin, phenols and glycosides. Gas Chromatography and Mass Spectroscopy (GCMS) study revealed the presence of therapeutic compounds like octadecenoic acid methyl ester, deoxyspergualin and eicosatrienoicacid. The extract assessed for its α–amylase and α–glucosidase inhibition inhibition at a dose of 20 - 100 µg/ml, at 5% level of significance on both antidiabetic activities were observed. Further the results of in vitro antioxidants (DPPH radical, superoxide and nitricoxide radical) scavenging activities confirmed their antioxidant potentials with the IC50 values of 326, 345 and 248 µg/ml, respectively. Bangladesh J. Bot. 52(3): 783-789, 2023 (September)